BEHAVIORAL ASPECTS IN COMMUNITY ORAL HEALTH PROBLEMS: A STUDY ON DENTAL TREATMENT DISCONTINUATION - Felix Aryadi Joelimar (Faculty of Dentistry, Universitas Indonesia, 2015)
The low value of F/DMF-T ration on Performed Treatment Index in Indoneisa gives an indication of great problems in dental treatment utilization. Dental treatment utilization is affected by several obstacles, the greatest among which is psychosocial obstacles. In this study the psychosocial obstacles were detected through Intrinsic Obstacles, Obstacles in Transportation, and Obstacles in Dental Clinic related to their effects on their discontinuation of dental treatments at Balkesmas Kiara, Kecamatan Senen, Jakarta Pusat. The discontinuation of dental treatments was mostly affected by Intrinsic Obstacles, through its components as Types of Cases, Dental Anxiety Scale, and Intrinsic Motivation. Generally Obstacles in Transportation had no effects, excpet its components of Travel Time and Tiredness. Obstacles in Dental Clinic had a significant effect on the discontinuation of dental treatments through the unpleasant manner of the druggist, the hot waiting room, and the high expense on drugs.